Changes in Tomato Fruit Quality and Antioxidant Enzyme Activities under Deficit Irrigation and Fertilizer Application in a Solar Greenhouse in Northwest China. Issue 10 (30th May 2016) - Mu, Lan; Fang, Lan
ABSTRACT: The interaction between water availability in the soil and fertilizer application rates often strongly affects crop growth. In the current study, the quality of fresh fruit and antioxidant enzymes of tomato crops ( Lycopersicon esculentum Mill) were investigated under different irrigation (low water content [Wl ]: 50 60% field moisture capacity (FMC); moderate [Wm ]: 70 80% FMC; and high [Wh ]: 90 100% FMC) and fertilizer conditions (deficit fertilizer [Fl ]: 195 kg ha −1 nitrogen (N) + 47 kg ha −1 phosphorus pentoxide (P2 O5 ) and moderate [Fm ]: 278 kg ha −1 N + 67 kg ha −1 P2 O5 ) in a solar greenhouse. The results showed that the quality of fresh fruits and the antioxidant enzyme activities in the leaves and fruits were related to the water content in the soil. Deficit irrigation improved the fruit quality and 50 60% FMC combined with fertilizer application rates of 195 kg ha −1 N + 47 kg ha −1 P2 O5 is recommended for tomato crop cultivation under greenhouse conditions.